APPLICATION OF ANTIOXIDANTS AND EDIBLE STARCH COATING TO REDUCE BROWNING OF MINIMALLY-PROCESSED CASSAVA - Coelho, Daniel Gomes (2017)
This study aimed to evaluate the quality of minimally-processed cassava treated with antioxidants and a starch-based edible coating. Cassava roots were washed, cooled, immersed in cold water, peeled and then cut. Root pieces were then immersed in a chloride solution, centrifuged, and subsequently immersed in either a starch suspension (3%), a solution containing antioxidants (3% citric acid and 3% ascorbic acid), or in both the coating and antioxidant solutions. Coated root pieces were dried at 18 ± 2°C for 1 hour, then packaged into polypropylene bags (150 g per pack) and kept at 5 ± 2°C for 15 days, and assessed every 3 days. A completely randomized design was used in a 4 × 6 factorial consisting of the treatment (control, coating, antioxidant, or coating and antioxidant) and the storage period (0, 3 6, 9, 12 or 15 days), with three replicates in each group. The pH, blackened area and peroxidase and polyphenol oxidase activities of the cassava was reduced in treatments containing antioxidants and the scores of visual analysis and phenolic content were higher. Therefore, treatment with antioxidants was effective for reducing browning in minimally-processed cassava, retaining the quality of cassava pieces stored for 15 days at 5 ± 2°C. The combination of antioxidants and the edible coating showed no improvement compared to treatment with antioxidants alone.